PENGEMBANGAN MODEL TALKING STICKS DALAM KETERAMPILAN BERBICARA BAHASA INGGRIS PADA SISWA KELAS X (IPA 1) DI SMAN 4 BANGKALAN- MADURA - Wahyudi, Moh. Arief (Universitas Nahdatul Ulama Surabaya, 2017)
There is a learning model that can help teachers in class X of Senior high schools in the field of study of the English language namely a Talking Sticks Model. The researchers used a Descriptive Qualitative method with the instrument of observation check list by three meeting times. Generated data that the total number of scores on the answer